Game Battleship Menggunakan Metode BFS dan Database Firebase Dengan Unity Pada Android - Yosep Mikie Prasetiyo; Djoni Haryadi Setiabudi; Anita Nathania Purbowo (Jurnal Infra, 2018)
The game is already a daily activity of the community. There are several types of games but the most playable game types today are mobile games where they can be played wherever and whenever. This thesis aims to perform the manufacture and similar research on mobile game battleship. Legitimate research has been done about battleship games on the PC platform by using LAN network. In this thesis will examine about mobile game battleship using BFS method and firebase database on mobile phone platform. The problem of this research is to measure how successful the application of BFS method and the implementation of firebase database used for multiplayer.In this battleship game research has been done the application process is the application of BFS method, and the application of firebase database. Process Where application on BFS method is done on program coding only. However, the application of firebase database is done by connecting Unity program with firebase SDK which is assisted by database calling on the program.Through testing it can be proven that the use of the BFS method of finding a very long route will take considerable time. For Firebase the database is less suitable for battleship action game where the mobile phone used to access the game can not receive data submissions sent from the database.